Variations in Crustal and Uppermost Mantle Structures Across Eastern Tibet and Adjacent Regions: Implications of Crustal Flow and Asthenospheric Upwelling Combined for Expansions of the Tibetan Plateau. Issue 8 (24th August 2019) - Zheng, Chen; Zhang, Ruiqing; Wu, Qingju; Li, Yonghua; Zhang, Fengxue; Shi, Kexu; Ding, Zhifeng
Abstract: We present new, high‐resolution constraints on crustal and uppermost mantle structure of the southeastern, eastern, and northeastern Tibetan plateau and adjacent regions by combining extensive data from three regional‐scale dense seismic arrays. Our results show significant differences in the crustal and uppermost mantle structure within the Songpan‐Ganzi terrane. The southern part has a thick crust and high Poisson's ratio, while the crustal thickness becomes less and Poisson's ratio is nearly normal in the northeast. Prominent low‐velocity anomalies appear beneath both the southern and northeastern Songpan‐Ganzi terrane at depths of 20–40 km, but they are not interconnected. Seismic velocities of the uppermost mantle are slow in the northeastern Songpan‐Ganzi terrane relative to the south. We further find that the crust of the central Qilian orogen is thickened but with remarkable low Poisson's ratio. Low velocities are visible in both the mid‐lower crust and uppermost mantle, similar to the northeastern Songpan‐Ganzi terrane. For comparison, the crustal low velocities are less pronounced beneath the central Qilian orogen. High Poisson's ratio and the mid‐lower crustal anomaly of the southern Songpan‐Ganzi terrane strongly indicate partial melting of the crust. Localized asthenospheric upwelling, however, can account for the coincident anomalies in both the mid‐lower crust and uppermost mantle beneath the northeastern Songpan‐Ganzi terrane and central Qilian orogen. We conclude that outward expansion of the Tibetan plateau has evolved by a combination of crustal flow on its southeastern margin and mantle upwelling likely induced by removal of thickened lithosphere on its easternmost and northeastern edges. Key Points: Variation in crustal and uppermost mantle structures within the Songpan‐Ganzi terrane The crustal and uppermost mantle structures are correlated beneath the northeastern Songpan‐Ganzi terrane and central Qilian orogen Tibet has evolved by crustal flow on its southeastern margin and localized mantle upwelling on its easternmost and northeastern edges